Soluble Cripto-1 Induces Accumulation of Supernumerary Centrosomes and Formation of Aberrant Mitoses in Human Embryonic Stem Cells - Porokh, Volodymyr; Vaňhara, Petr; Bárta, Tomáš; Jurečková, Lucie; Bohačiaková, Dáša; Pospíšilová, Veronika; Mináriková, Daniela; Holubcová, Zuzana; Pelková, Vendula; Souček, Karel; Hampl, Aleš (Stem cells and development, 2018)
Chromosomal instability evoked by abnormalities in centrosome numbers has been traditionally considered as a hallmark of aberrant, typically cancerous or senescent cells. We have reported previously that pristine human embryonic stem cells (hESC) suffer from high frequency of supernumerary centrosomes and hence may be prone to undergo abnormal mitotic divisions. We have also unraveled that this phenomenon of multicentrosomal mitoses vanishes with prolonged time in culture and with initiation of differentiation, and it is strongly affected by the culture substratum. In this study, we report for the first time that Cripto-1 protein (teratocarcinoma-derived growth factor 1, epidermal growth factor-Cripto/FRL-1/Cryptic) produced by hESC represents a factor capable of inducing formation of supernumerary centrosomes in cultured hESC. Elimination of Cripto-1 signaling on the other hand restores the normal number of centrosomes in hESC. Linking the secretory phenotype of hESC to the centrosomal metabolism may help to develop better strategies for propagation of stable and safe bioindustrial and clinical grade cultures of hESC. From a broader point of view, it may lead to unravelling Cripto-1 as a micro-environmental factor contributing to adverse cell behaviors in vivo.
Keywords: mezibuněčné signální peptidy a proteiny; signální transdukce; buněčná diferenciace; nádorové proteiny; GPI-Linked Proteins; Signal Transduction; lidské embryonální kmenové buňky; Human Embryonic Stem Cells; lidé; mitóza; Humans; Centrosome; Mitosis; GPI-vázané proteiny; centrozom; Intercellular Signaling Peptides and Proteins; Neoplasm Proteins; Cell Differentiation